Comparison of the clinical results of isolated Bankart and SLAP 5 lesions after arthroscopic repair - Sarıkaya, Baran (Jt Dis Relat Surg, 2020)
OBJECTIVES: This study aims to compare the clinical results of patients with traumatic isolated Bankart lesions and type V superior labrum anterior to posterior (SLAP) lesions after arthroscopic repair. PATIENTS AND METHODS: Patients who underwent arthroscopic repair for traumatic anterior glenohumeral instability were evaluated retrospectively between December 2014 and January 2019. Fifty-one patients (49 males, 2 females; mean age 25 years; range, 18 to 36 years) without bone defects affecting >20% of the glenoid fossa, off-track engaging Hills-Sachs lesions, multidirectional instability, or ligamentous laxity were included in the study. Group 1 had 31 patients with isolated Bankart lesions and group 2 had 20 patients with type V SLAP lesions. There were only two female patients in group 1 and all patients were male in group 2. The mean age was 25 years (range, 18 to 36 years) in group 1 and 25 years (range, 19 to 35 years) in group 2. Rowe, Constant, and Western Ontario Shoulder Instability (WOSI) scoring systems were used to evaluate the clinical outcomes of the patients preoperatively and at the last follow-up. RESULTS: The mean follow-up time was 32 months (range, 12 to 48 months) in group 1 and 28.5 months (range, 12 to 42 months) in group 2. There were no statistically significant differences between the two groups in terms of the number of shoulder dislocations before the surgery, mean age at the time of surgery, and the mean time from the first dislocation to surgical treatment. When the Rowe, Constant, and WOSI scores were evaluated preoperatively and at the last follow-up, there were statistically significant changes within, but not between, the two groups. CONCLUSION: In type V SLAP lesions, the affected and repaired labrum surface area is larger than isolated Bankart lesions. However, as a result of appropriate surgical treatment, the affected surface area does not have a negative effect on clinical outcomes, and similar clinical results can be obtained in patients with type V SLAP lesions compared to patients with isolated Bankart lesions.